Thrombocytopenia in Guinea Pigs Infected by Encephalomyocarditis Virus (EMC) - Modai, Y; Oren, R; de Vries, A; Kohn, A (Thrombosis and Haemostasis, 1967)
Intraperitoneal infection of guinea pigs with Encephalomyocarditis (EMC) virus led to viremia 2-10 days after infection and to paralysis and death of some of the infected animals. During the course of infection there was marked leucocytosis and thrombocytopenia. No abnormalities were detected in megakaryocytes in bone marrow cultures from infected guinea pigs. Exposure of guinea pig bone marrow culture to EMC virus in vitro impaired granulation and disintegration of megakaryocytes to platelets.